Slawistik an der deutschen Universitaet in Prag (1882-1945) - Zeil, Wilhelm (Marburger Abhandlungen zur Geschichte und Kultur Osteuropas, 1995)
The present monograph provides an inventory and a current account of about half a century of Slavic studies, Slavic research and teaching, at the German University in Prague. It assumes, in the sense of the futuristic programs of Heinrich Felix Schmid and Reinhold Trautmann (1927), Franz Spinas and Gerhard Gesemanns (1928) as well as Maximilian Braun (1949), of a comprehensive concept of Slavic, which in addition to Slavic philology the history of Slavic peoples and the history of German-Slavic spiritual-cultural relations.